Dimensionality of an adapted Authentic Leadership Questionnaire: Three independent South African studies - Anton Grobler; Sonja Grobler (SA Journal of Industrial Psychology)
Orientation: Authentic leadership (AL) is a well-defined construct and measured by instruments mostly developed and validated in the United States and Europe.